Hybrid Enzymatic/Photocatalytic Degradation of Antibiotics via Morphologically Programmable Light‐Driven ZnO Microrobots. Issue 39 (26th August 2022) - Oral, Cagatay M.; Ussia, Martina; Pumera, Martin
Abstract: Antibiotics are antimicrobial substances that can be used for preventive and therapeutic purposes in humans and animals. Their overdose usage has led to uncontrolled release to the environment, contributing significantly to the development of antimicrobial resistance phenomena. Here, enzyme‐immobilized self‐propelled zinc oxide (ZnO) microrobots are proposed to effectively target and degrade the released antibiotics in water bodies. Specifically, the morphology of the microrobots is tailored via the incorporation of Au during the synthetic process to lead the light‐controlled motion into having on/off switching abilities. The microrobots are further modified with laccase enzyme by physical adsorption, and the immobilization process is confirmed by enzymatic activity measurements. Oxytetracycline (OTC) is used as a model of veterinary antibiotics to investigate the enzyme‐immobilized microrobots for their removal capacities. The results demonstrate that the presence of laccase on the microrobot surfaces can enhance the removal of antibiotics via oxidation. This concept for immobilizing enzymes on self‐propelled light‐driven microrobots leads to the effective removal of the released antibiotics from water bodies with an environmentally friendly strategy. Abstract : An environmentally friendly removal strategy is presented toward the released antibiotics in water bodies. To this end, self‐propelled zinc oxide (ZnO) microrobots are utilized as solid supports for enzyme immobilization. The results demonstrate that photocatalytic degradation and active motion features of light‐driven microrobots can be combined with enzymatic degradation to enhance the removal of antibiotics.